(untitled) (KULT_online, 2017)
Klang – Kontakte. Kommunikation, Konstruktion und Kultur von Klängen (Isa-Lohmann-Siems publication series, Vol. 9) is a multidisciplinary publication edited by Anna Symanczyk, Daniela Wagner, und Miriam Wendling. 13 contributions differing in methodological, historical, and content-related perspectives aim at understanding and exploring mediating aspects of sound in cultural communication processes. Within this context, it is especially transformation into and representation of sounds in language, text, and images that are key subjects of research in this volume. As a humanities-based anthology, this volume supplements the research field of sound studies, which is relatively young compared to the fields of the psychology of music and psycho-acoustics, and offers discipline-specific impulses.